What is required to scale-up and sustain biofortification? Achievements, challenges and lessons from scaling-up Orange-Fleshed Sweetpotato in Sub-Sahara Africa - Mulongo, G.; Munyua, H.M.; Mbabu, A.N.; Maru, J. (Elsevier, 2021)
This review presents results of the ex-post survey on Reaching Agents of Change (RAC) project, highlightingexperiences, lessons, challenges and recommendations for scaling up orange-fleshed sweetpotato (OFSP). TheRAC project was a three-and halfyear initiative (2011 and 2015), implemented in three primary countries, namelyTanzania, Mozambique, Nigeria, and to a lesser extent Ghana and Burkina Faso. The project advocated for policychange and increased investments to scale-up the orangefleshed sweetpotato (OFSP) to combat vitamin A defi-ciency. RAC planned to generate new investments totaling US$ 18 million for OFSP activities in the three years ofits life but exceeded this target by 20%. RAC further expected to benefit at least 600,000 households directly andis currently on track, having reached 309,974 direct beneficiaries (of whom 20.3% were women). The RACexperience demonstrated a potential scaling-up model for biofortified crops based on the hypothesis that scalingup can be achieved through supportive policies (and investments), strong institutional capacities and appropriateinnovative technologies working through a partnership of governmental and non-governmental organizations andcivil society.